ANALISIS PENGARUH CAR, FDR, BOPO, BANK AGE, DAN SUKU BUNGA TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH INDONESIA PERIODE 2015-2019 - Ikrom, Ahmadul; Syaichu, Muhamad (Diponegoro Journal of Management, 2024)
ABSTRACT This research aimed to examine the influence of Capital Adequacy Ratio (CAR), Financing to Deposite Ratio (FDR), Operating Costs and Operating Income (BOPO), Bank Age, Interest Rates (SBI) on the financial performance of sharia banking registered on the Financial Services Authority (OJK). Bank financial performance was measured by Return on Assets (ROA). .The population used in this research was sharia banking registered on the Financial Services Authority (OJK) for the 1st quarter 2015 to 4th quarter 2019 period. The number of samples used was 11 sharia banks which were taken using the purposive sampling method. The analysis method used was panel data regression with STATA 17 as a data processing tool. The research results showed that the influence of the Capital Adequacy Ratio (CAR), Financing to Deposite Ratio (FDR), Operational Costs and Operational Income (BOPO), Bank Age, and Interest Rates (SBI) had a significant effect on financial performance (ROA) simultaneously. As partial, Adequacy Ratio (CAR) and Financing to Deposite Ratio (FDR) had a positive and significant effect on ROA, Operational Costs and Operating Income (BOPO), and Interest Rates (SBI) had a negative and significant effect on ROA, while Bank Age had no significant effect to ROA.